(untitled) (Società e diritti, 2020)
The emeritus professor of the San Marcos University, Dennis Chavez de Paz illustrates the method of data analysis for socio-legal research, starting from the definition of the variables and gradually through the illustration of the detection techniques and processing of sociologically relevant data